Atypical clinical presentation of Ebola virus disease in pregnancy: Implications for clinical and public health management. (August 2020) - Pavlin, Boris I.; Hall, Andrew; Hajek, Jan; Raja, Muhammad Ali; Sharma, Vikas; Ramadan, Otim Patrick; Mishra, Sharmistha; Rangel, Audrey; Kitching, Aileen; Roper, Katrina; O'Dempsey, Tim; Starkulla, Judith; et al.
Highlights: Pregnant women infected with Ebola virus may present atypically. Current Ebola virus disease case definitions are inappropriate for pregnant women. Infected newborns may appear asymptomatic despite being potentially infectious. Obstetric care during an Ebola outbreak requires heightened precautions. Pregnant contacts of Ebola-infected individuals require special considerations. Abstract: Background: Between December 2013 and June 2016, West Africa experienced the largest Ebola virus disease (EVD) outbreak in history. Understanding EVD in pregnancy is important for EVD clinical screening and infection prevention and control. Methods: We conducted a review of medical records and EVD investigation reports from three districts in Sierra Leone. We report the clinical presentations and maternal and fetal outcomes of six pregnant women with atypical EVD, and subsequent transmission events from perinatal care. Results: The six women (ages 18–38) were all in the third trimester. Each presented with signs and symptoms initially attributed to pregnancy. None met EVD case definition; only one was known at presentation to be a contact of an EVD case. Five women died, and all six fetuses/neonates died. These cases resulted in at least 35 additional EVD cases. Conclusions: These cases add to the sparse literature focusing on pregnant women with EVD, highlighting challenges and implications for outbreak control. Infected newborns may also present atypically and may shed virus while apparently asymptomatic. Pregnant women identified a priori as contacts of EVD cases require special attention and planning for obstetrical care.